Relationship Self-Disclosure With Anxiety In Compiling Student Thesis Study Program Primary School Teacher Education - Nurdin Arifin (Universitas Pahlawan Tuanku Tambusai, 2021)
Anxiety problems in natural semester students who finish the thesis need to be overcome. Disclosing personal information to others to complete the final assignment performed by the student is an intentional or accidental act in action. This Self-disclosure is a process of making students be known by others who generate knowledge between themselves and others. The purpose of this research is to explain the self-disclosure and anxiety relationship of students in completing the final task, moreover, will be a teacher so that it can control anxiety in him. Where the research subjects of 110 PGSD students widya gama mahakam Samarinda university with sampling techniques, namely purposive sampling. Self-disclosure students are in the moderate category with an average of 114.15 and student anxiety in completing the thesis is in the medium category with an average of 93.53. The results showed that the correlation coefficient was rxy=-0.192. The correlation value indicates a negative direction which means that the lower self-disclosure then, the higher the student's anxiety in composing the thesis. It can also be said that the higher the self-disclosure, the lower the student's anxiety in composing the thesis.